Biological Activity of the Water Soluble Complex trans-dichloro-1,2-propylenediamine-N,N,N,N-Tetraacetato Ruthenium (III) (RAD) - Delmani, Fatima Azzahra; Jaran, Adnan; Torreblanca, José; Moreno, Javier; García-Herdugo, Gregorio; Vilaplana, Rosario; González-Víltchez, Francisco (Asian Journal of Biological and Life Sciences, 2016)
In this study we investigated the effect of the new antitumor complex trans-[RuLCl2]H.4H2O (RAD) on cultured TG cells (a human ovarian cell line), we found that RAD was cytotoxic to these cells. RAD was shown to interact with DNA of these tumour cells causing damage which was assessed by the comet assay. This interaction was causing a modification in the expression of certain nucleolar proteins, UBF (upstream binding factor) an RNA polymerase I-specific transcription factor involved in the recognition of the ribosomal RNA gene promoter and initiating transcription, and fibrillarinwhich contributes in many post transcriptional processes such as pre-rRNA processing, pre-rRNA methylation, and ribosome assembly.We found,after immunoprecipitating these two proteins, that the 2 isoforms of the protein UBF were expressed differently in TG cell extracts treated with RAD with a major abundance of UBF1 compared with the control untreated cells, and little expression of UBF2 when treated with RAD compared with the control. Fibrillarin was present in high quantities in TG protein extracts treated with RAD compared with the control. Comparing these results with the cis form of the compound (RAP), we found similar results regarding DNA damage but different results regarding protein expression. Although RAP was more powerful than RAD, the latest could be a good candidate as a potential antitumour drug used in the treatment of cancer.
Keywords: Antitumor drugs; Comet assay; Fibrillarin; Immunoprecipitation; RAD; RAP; UBF